INFLUENCE OF PRIMING TECHNIQUES ON EMERGENCE AND SEEDLING GROWTH OF FORAGE SORGHUM (Sorghum bicolorL.) - M. Shehzad; M. Ayub; A. U. H. Ahmad; M. Yaseen (Journal of Animal and Plant Sciences, 2012)
Seed priming is a technique which improves the germination and early growth under prevailing environmental conditions. However, the information on seed priming in sorghum is lacking in Pakistan. Therefore, this study was designed to evaluate the effects of different seed priming techniques, un-soaked seed (control), Hydro-priming (soaked with distill water), Halopriming with KNO3 and CaCl2 (1% solution), on seed emergence and seedling growth of three sorghum genotypes (Hegari, JS-263 and JS-2002). Experiment was conductedin wire house under natural climatic conditions during 2008. All the priming treatments significantly affected the fresh weight, shoot length, number of roots, root length, vigor index, time to start emergence, time to 50% emergence and energy of emergence of forage sorghum. The interactive effect of varieties and priming techniques were not significant for mean emergence time and coefficient of uniformity of emergence. It is concluded that seed priming may serve as an appropriate treatment for accelerating the emergence of sorghum genotypes studied.
Keywords: seed priming; emergence; seedling growth; sorghum.